Rural endogenous development: a strategy for the post-emu european agriculture - Romano D. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
The implementation of the new Common Agricultural Policy (CAP) in the European Union (EU) in early nineties has brought about far-reaching consequences for rural development. Among others, the farmer, liberating himself from his one and only role of producer, can profit from the opportunities offered by other activities that are complementary and alternative to agriculture: Thus the farmer has an essential role in the valorization of endogenous resources of the area where he carries his activities on. This phenomenon has been analyzed mainly within the so-called 'endogenous development' (ED) paradigm. ED patterns are founded mainly, though not exclusively, on locally available resources, such as the potentialities of the local environment, labor force, knowledge, and local patterns for linking production to consumption, etc. While ED is still not a well defined paradigm, it seems to have some nice explanatory categories which could be worth to discuss. This is the main purpose of such a research, i.e. how the idea of ED has emerged and what it is.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)